Lipid accumulation product is a predictor of nonalcoholic fatty liver disease in childhood obesity - Bahar Özcabı; Salih Demirhan; Mesut Akyol; Hatice Öztürkmen Akay; Ayla Güven (Korean Pediatric Society, 2019)
Background Lipid accumulation product (LAP) is associated with the presence and severity of nonalcoholic fatty liver disease (NAFLD) in adults. Purpose Here we evaluated the ability of LAP to predict NAFLD in obese children. Methods Eighty obese children (38 girls; age 6-18 years) were included. Anthropometric measurements and biochemical values were obtained from the patients' medical records. LAP was calculated as [waist circumference (WC) (cm) - 58]×triglycerides (mmol/L) in girls; [WC (cm) - 65]×triglycerides (mmol/ L) in boys. The minLAP and adjLAP were described (3% and 50% of WC values, respectively) and the total/high-density lipoprotein cholesterol index (TC/HDL-C) was calculated. NAFLD was observed on ultrasound, and patients were divided into 3 groups by steatosis grade (normal, grade 0; mild, grade 1; moderate-severe, grade 2-3). The area under the curve (AUC) and appropriate index cutoff points were calculated by receiver operator characteristic analysis. Results LAP was positively correlated with puberty stage (rho=0.409; P<0.001), fasting insulin (rho= 0.507; P<0.001), homeostasis model assessment of insulin resistance (rho=0.470; P<0.001), uric acid (rho=0.522; P<0.001), and TC/HDL-C (rho=0.494; P<0.001) and negatively correlated with HDL-C (rho=-3.833; P<0.001). LAP values could be used to diagnose hepatosteatosis (AUC=0.698; P=0.002). The LAP, adjLAP, and minLAP cutoff values were 42.7 (P=0.002), 40.05 (P=0.003), and 53.47 (P= 0.08), respectively. For LAP, the differences between the normal and mild groups (P=0.035) and the normal and moderate-severe groups were statistically significant (P=0.037), whereas the difference between the mild and moderate-severe groups was not (P>0.005). There was a statistically significant difference between the normal and mild groups for adjLAP (P=0.043) but not between the other groups (P>0.005). There was no significant intergroup difference in minLAP (P>0.005). Conclusion LAP is a powerful and easy tool to predict NAFLD in childhood. If LAP is ≥42.7, NAFLD should be suspected. This is the first study to assess LAP diagnostic accuracy for childhood obesity.